An Ecosystem-Based Approach to Evaluating Impacts of Fisheries Management on Ecosystem Restoration in a Chinese Subtropical Yangming Reservoir - Haibo Gong; Chengjie Yin; Jinxiang Yu; Jun Xiao; Zhijie Yu; Xuejun Fu; Bin Huang; Xiya Wu; Caigang Li (Fishes, 2025)
This study delves into the ecological implications of diverse fishery patterns on aquatic ecosystems, centering on environmental parameters, species richness, and nutrient dynamics. Using the ecological fishery management model of Yangming Lake as a case, it evaluates its influence on water quality improvement, species diversity promotion, and ecosystem stability maintenance. From 2018 to 2022, the Shannon–Wiener index in Yangming Lake increased by 17.34%, and water quality significantly improved, with phytoplankton biomass decreasing by 95.5%, total nitrogen content dropping by 33.69%, and permanganate index declining by 30.75%. Although ecological fisheries demonstrate certain effectiveness in tackling invasive species, further in-depth research is needed. This study emphasizes the importance of striking a balance between fishery development and ecological protection, in line with the United Nations Food and Agriculture Organization’s “blue transformation” strategy. Our findings offer valuable insights for sustainable fisheries development and highlight the necessity of customized management strategies to protect biodiversity and ecosystem resilience. Future research will focus on exploring the long-term ecological effects of ecological fisheries and the role of native carnivorous fish in controlling invasive species.